Correction of immunosuppression in aged septic rats by human ghrelin and growth hormone through the vagus nerve-dependent inhibition of TGF-β production - Mian Zhou; Monowar Aziz; Mahendar Ochani; Ping Wang (BMC, 2020)
Abstract Background Co-administration of human ghrelin and growth hormone (GH) reverse immunosuppression in septic aged animals, but the mechanism remains elusive. Here, we hypothesize that ghrelin and GH co-treatment restores the immune response in aged septic rats by inhibiting the production of transforming growth factor-β (TGF-β), an immunoregulatory cytokine, through the vagus nerve. Methods Male aged Fischer rats (22-23-month-old) were made septic by cecal ligation and puncture (CLP) with or without dissecting the vagus nerve (vagotomy). Human ghrelin and GH or vehicle (PBS) were administrated subcutaneously at 5 h post CLP. After 20 h of CLP, serum and spleens were harvested. Results Serum TGF-β levels were increased in septic aged rats, while ghrelin and GH treatment significantly reduced its levels. Expression of TGF-β in the spleen was upregulated after sepsis, while ghrelin and GH treatment significantly inhibited its expression. TNF-α and IL-6 levels were significantly reduced after ex vivo LPS stimulation of splenocytes from rats that underwent CLP compared to sham rats; while these levels were significantly higher in splenocytes from ghrelin and GH-treated CLP rats compared to vehicle-treated CLP rats. Ghrelin and GH treatment reduced program death receptor-1 (PD-1) expression, increased human leukocyte antigen-DR (HLA-DR) expression, attenuated lymphopenia, and cleaved caspase-3 levels in the spleen of septic aged rats. Vagotomy diminished the beneficial effects of ghrelin and GH treatment in septic rats. In vitro, the addition of ghrelin, GH, or ghrelin and GH together had no effect on restoring immune response in splenocytes from CLP rats following LPS stimulation, indicating the requirement of the vagus nerve for ghrelin and GH's effect. Conclusions Ghrelin and GH attenuate immunosuppression in aged septic rats through the vagus nerve-dependent inhibition of TGF-β production.